1993
DOI: 10.1149/1.2056170
|View full text |Cite
|
Sign up to set email alerts
|

Selective Wet Etching of GaInP , GaAs , and InP in Solutions of HCl ,  CH 3 COOH  , and  H 2 O 2

Abstract: The wet chemical etching of GaInP, GaAs, and InP in solutions of HCl:CH3COOH:H20= has been evaluated. In the absence of the oxidant, H202, the solutions etch tnP and GaInP with high selectively over GaAs but rough surfaces are formed. When H202 is added, smoother surfaces are obtained and depending on the H202 concentration, the etchant can be made highly selective for GaAs. The etch rate of these mixtures varies strongly with the age of the solution, initially increasing and then gradually declining. The incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 2 publications
2
18
0
Order By: Relevance
“…The achievement of a smooth mesa is essential for an effective study of the surface passivation since surface recombination depends on the smoothness of the etched surface. Flemish and Jones [13] reported that various combinations of HCl:CH 3 COOH:H 2 O 2 can be used to etch the III-V materials slowly and smoothly for optoelectronic device applications. In this work, an etch solution of composition HCl:CH 3 COOH: H 2 O 2 ::6:4:1 at 2 C has been used for mesa etching.…”
Section: Methodsmentioning
confidence: 99%
“…The achievement of a smooth mesa is essential for an effective study of the surface passivation since surface recombination depends on the smoothness of the etched surface. Flemish and Jones [13] reported that various combinations of HCl:CH 3 COOH:H 2 O 2 can be used to etch the III-V materials slowly and smoothly for optoelectronic device applications. In this work, an etch solution of composition HCl:CH 3 COOH: H 2 O 2 ::6:4:1 at 2 C has been used for mesa etching.…”
Section: Methodsmentioning
confidence: 99%
“…Typically, the oxidizing agents are hydrogen peroxide (H 2 O 2 ) and potassium dichromate (K 2 Cr 2 O 7 ), and the oxide-dissolvers are ammonium hydroxide (NH 4 OH), [3][4][5][6][7] sulfuric acid (H 2 SO 4 ), 8) phosphoric acid (H 3 PO 4 ), 9,10) hydrofluoric acid (HF), [11][12][13] bromine (Br 2 ), 14) citric acid 15,16) and hydrogen chloride (HCl). 17,18) Water (H 2 O), methanol (CH 3 OH), and ethanol (C 2 H 5 OH) are commonly used as diluents to control the etchant concentration. 19) Acetic acid (CH 3 COOH) has been used to dilute etchants made of strong acids as a buffer solution, because CH 3 COOH is a weak acid with a lower reactivity.…”
Section: Principle Of Gaas Wet Etchmentioning
confidence: 99%
“…19) Acetic acid (CH 3 COOH) has been used to dilute etchants made of strong acids as a buffer solution, because CH 3 COOH is a weak acid with a lower reactivity. 17,18) Sodium hypochlorite (NaOCl) can also be used alone or mixed with other solutions, because NaOCl has the functions of both oxidation and reduction. 20) Possible cross section profiles of (001) GaAs by the above aqueous etchants are shown in Fig.…”
Section: Principle Of Gaas Wet Etchmentioning
confidence: 99%
“…The etching rate for InP and InGaAsP was proportional to t 0.6~0.8 at about 20°C, were t is the etching time. 19 The increase in the etch rate with etching time was attributed to the formation of Cl 2 Orientation dependent etching of photolithographically patterned ( 1 1 1 ) GaP was investigated using solutions of HCl:CH 3 COOH:H 2 O 2 . 17 The chemical etching characteristics for the (001) planes of InGaAsP/ InP double heterostructure wafers were studied using SiO 2 masking in the same solution.…”
Section: Introductionmentioning
confidence: 99%